Pay Roll Taxation and Employment Stabilization - Lindblom, Charles E. (Quarterly Journal of Economics, 1943)
Journal Article Pay Roll Taxation and Employment Stabilization Get access Charles E. Lindblom Charles E. Lindblom University of Minnesota Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 57, Issue 4, August 1943, Pages 657–658, https://doi.org/10.2307/1884660 Published: 01 August 1943